Comparative study of the usefulness of risk score assessment in the early stages of COVID‐19 affected pregnancies: Omicron variant versus previous variants. Issue 11 (5th August 2022) - Magawa, Shoichi; Nii, Masafumi; Maki, Shintaro; Enomoto, Naosuke; Takakura, Sho; Kusaka, Naoko; Maegawa, Yuka; Osato, Kazuhiro; Tanaka, Hiroaki; Kondo, Eiji; Ikeda, Tomoaki
Abstract: Aim: To evaluate the utility of the risk score in assessing the current status and prognosis of COVID‐19 in pregnancy. Methods: Seventy‐seven cases affected before the Omicron variant epidemic and 50 pregnant cases affected by the Omicron variant were included. The risk score consists of maternal background, current condition, and examination findings. We determined the risk score in the early stages of disease onset. Results: There were no significant differences in the maternal or gestational ages between the groups. The risk score was significantly lower in the After‐Group patients (those affected during the Omicron epoch), while 14.3% of the Before‐Group patients (those affected during the pre‐Delta and Delta epochs), experienced a worsening of disease after the visit to the center, whereas none of the After‐Group patients did. The Before Group's frequency of risk score items was higher among the two groups for "fever for ≥48 h, " "mild pneumonia image, " and "blood tests, " whereas "disease onset 14 days after the second vaccination" was increased in After Group. The blood test parameters for platelet count, C‐reactive protein, and D‐dimer levels were not significantly different between the groups. Conclusions: The risk score system appeared superior in detecting deteriorating cases. There were no cases of post‐illness deterioration in the After‐Group, suggesting that cases of the Omicron variant in pregnancy may have had a less severe course compared to that of previous variants. However, there was no significant difference between the groups in terms of a specific blood test evaluation, suggesting the need for a combined evaluation of cases affected during pregnancy.